Cytotoxic Properties of Amino Acid Substituted Novel Cinnamic Acid Compounds - Caliskani, Eray; Ozturk, Dilara Altay; Tekin, Suat; Koran, Kenan; Gorgulu, Ahmet Orhan; Cetin, Ahmet (Wiley, 2019)
[Abstract Not Available]
Keywords: Amino acid; Cinnamic acid; A2780; MTT Assay; PC-3